PEMANFAATAN POSBINDU PTM OLEH PASIEN HIPERTENSI PESERTA BPJS KESEHATAN DI PUSKESMAS ARO: Utilization of PTM Posbindu by Hypertension Patients of BPJS Kesehatan Participants at Puskesmas Aro - Wahyu Ningsih, Nanda Reka; Sari, Rumita Ena; Wardiah, Rizalia; Ridwan, M.; Ivanti, Risty (Poltekes Kemenkes Tanjungpinang, 2021)
Hypertension is a disease that is described by an increase in blood pressure higher than the normal limit that lasts continuously for a long period of time. There are efforts to prevent and early detection of NCDs, namely the Integrated Development Post for Non-Communicable Diseases which is a form of community health-based effort under the guidance of the puskesmas in controlling PTM risk factors such as hypertension. This study aims to determine how the utilization of PTM Posbindu by hypertensive patients participating in BPJS Health at Aro Health Center in 2021. This study is a quantitative study with a cross sectional approach. The sampling technique used is simple random sampling. Data was collected by interview with a sample of 83 people. The results showed that there was a relationship between knowledge (p value = 0.019), and cadre support (p value = 0.010), with the utilization of PTM Posbindu by hypertension patients participating in BPJS Kesehatan at Aro Health Center in 2021. Be supposed to the puskesmas and cadres will work well together in preparing all matters related to activities to increase community participation in the utilization of PTM posbindu.